Submarine canyons as key habitats to preserve Risso’s dolphin (Grampus griseus) populations in the northwestern Mediterranean Sea - Chicote, Carla A.; Amigó, Natalia; Gazo, Manel (Frontiers in Marine Science, 2023)
This paper summarises the occurrence of Risso’s dolphin (Grampus griseus) over 12 years (2009 to 2021) in the northwestern Mediterranean. The study was conducted off the central coast of Catalonia (NE Spain) in an area covering 8,026 km2 and featuring a system of submarine canyons. The habitat is suitable for a wide diversity of species, including deep-diving cetaceans. In addition, a different dataset from other projects was included to compare distances to the coast from different periods. A visual effort of 8,756 km was carried out with the recording of 17 Risso’s dolphin sightings. The relative mean density of Risso’s dolphin was 0.0078 individuals/km2 (SD 0.1, n = 17), and the densities were higher in the southern canyons than in the northern canyons. Furthermore, the distance to the coast and the depth of any sighting were compared by gathering data from different periods and surveys (first period 1985–2014; second period 2016–2021) with 34 sightings analysed. Significant differences were found related to the distance to the coast, showing a displacement of the animals to more pelagic areas between periods. The spatial distribution of Risso’s dolphins was investigated by applying a generalized additive model based on sighting data collected during standardized vessel surveys. Four predictive variables were considered, taking into account the local physiographical features. The model showed that the spatial distribution of Risso’s dolphin in the area was related to the slope and slope variation. The species showed preferences for offshore areas as significant differences were obtained in terms of the distance of sightings to the coast. This paper provides new insights into the distribution of Risso’s dolphin in the central western Mediterranean Sea and identifies the submarine canyons of northern Catalonia as an essential habitat for the species.